Enrichment and fluorogenic labelling of 5-formyluracil in DNA. Issue 6 (3rd May 2017) - Liu, Chaoxing; Wang, Yafen; Zhang, Xiong; Wu, Fan; Yang, Wei; Zou, Guangrong; Yao, Qian; Wang, Jiaqi; Chen, Yuqi; Wang, Shaoru; Zhou, Xiang
Abstract : Biotinylated o -phenylenediamine directly tethered to naphthalimide can both enrich and fluorogenically label 5-formyluracil in DNA under physiological conditions. Abstract : Recently, the detection of natural thymine modified 5-formyluracil has attracted widespread attention. Herein, we introduce a new insight into designing reagents for both the selective biotin enrichment and fluorogenic labelling of 5-formyluracil in DNA. Biotinylated o -phenylenediamine directly tethered to naphthalimide can switch on 5-formyluracil, under physiological conditions, which can then be used in cell imaging after exposure to γ-irradiation. In addition, its labelling property caused the polymerase extension to stop in the 5-formyluracil site, which gave us more information than the fluorescence did itself. The idea of detecting 5-formyluracil might be used in the synthesis of other modified diaminofluoresceins.